Analysis of radiopacity, pH and cytotoxicity of a new bioceramic material - SOUZA, Letícia Chaves de; YADLAPATI, Mamatha; DORN, Samuel O; SILVA, Renato; LETRA, Ariadne (Journal of Applied Oral Science, 2015)
AbstractObjective RetroMTA® is a new hydraulic bioceramic indicated for pulp capping, perforations or root resorption repair, apexification and apical surgery. The aim of this study was to compare the radiopacity, pH variation and cytotoxicity of this material to ProRoot® MTA.Material and Methods Mixed cements were exposed to a digital x-ray along with an aluminum stepwedge for the radiopacity assay. pH values were verified after incubation period of 3, 24, 48, 72 and 168 hours. The cytotoxicity of each cement was tested on human periodontal ligament fibroblasts using a multiparametric assay. Data analysis was performed using ANOVA and Tukey’spost hoc in GraphPad Prism.Results ProRoot® MTA had higher radiopacity than RetroMTA®(p;0.05) although pH levels of both materials reduced over time. Both ProRoot® MTA and RetroMTA® allowed for significantly higher cell viability when compared with the positive control (p